Phase Noise Effects on the Performance of High‐Order Digital Modulation Terahertz Communication System. Issue 3 (1st May 2022) - DENG, Xianjin; YANG, Hao; WU, Qiuyu; JIANG, Jun; LIN, Changxing
Abstract : As the carrier frequency goes into the terahertz band, the phase noise of the signal source has increasing impacts on the performance of the communication system. Considering a 16QAM high‐order digital modulation terahertz communication system (DMTCS), by comparing the influence of two kinds of local oscillator signal sources with different phase noise characteristics on the bit error rate (BER) performance of the system based on theoretical analysis and experimental research, it is found that the near‐end phase noise of local oscillator signal source has a great influence on the BER performance of the DMTCS. The suppression of phase noise of the local oscillator signal source based on choosing loop bandwidth of the digital phase‐locked loop (DPLL) at the receiving end is also discussed. It is found that the negative impacts of phase noise on BER performance of the system can be efficiently decreased by reasonably selecting the loop bandwidth of the DPLL.